O potencial das biomassas como perspectiva de um modelo de economia circular para o Estado de Mato Grosso do Sul. - BARRETO, Claudia; MASCARENHAS, María; SANTIAGO, Felipe; BATISTOTE, Margareth (ANAIS DO ENIC, 2024)
-